Effectiveness of Flipboard as an Online Collaboration Tool for Teaching and Learning - Tarun, Ivy M. (11th International Scholars Conference, 2018)
This study assessed the effectiveness of Flipboard. Specifically, it described the demographic profile of the students; identified the perceived effectiveness of Flipboard; and identified the effectiveness of the Flipboard using Application Performance Index, Error Rate and Completion Rate. The study employed a descriptive research design where questionnaire-based and metrics-based approaches were used to address the study objectives. Students from the BSIT, BSCS and BSCpE were purposively selected as samples. Data gathered were analyzed using Frequency, weighted mean and ANOVA. Under this study, students are predominantly in BSIT program who are minor adult, female, owns smartphone, and have no personal computer and Internet access at home but with experience in using online collaboration tools. The students generally perceived that Flipboard is very effective as tool for collaboration, teaching and learning. On the other hand, Flipboard’s performance is poor based from Application Performance Index, but has good completion rate and least acceptable error rate. It is recommended that faculty members may integrate the use of Flipboard in classrooms as students generally find it very effective for collaboration, teaching and learning. Flipboard should be further enhanced by addressing errors to meet user satisfaction, and its effectiveness should be further evaluated using experimental approach.